O sistema de gêneros da seleção de candidatos a emprego no contexto empresarial - Conto, Janete Maria de (2008)
Studies in Genre Analysis have been developed with the aim of exploring the typification of genres of the work environment and interpreting their funtions according to the discursive communities in which they operate. Some examples are studies carried out by Bazerman (2005) and Devitt (1991) on documents from professional contexts. In that regard, Bazerman (2005) discusses notions such as genre, genre sets, genre systems and activity systems. Language practices in professional contexts have also been the object of investigations among Brazilian research teams, for instance LAEL at PUC/SP and PUC/RJ, in efforts to understand how the participants of a communicative event interact and how their lexicogrammatical choices construe meaning. In that sense, the present study approaches the system of genres adopted in the selective process for hiring a salesperson, conducted by a cooperative company in the state of Rio Grande do Sul. This system of genres comprises several texts: Want Ad, Presentation Letter, Curriculum Vitae and Interview. The objective of this study is to investigate the system of genres for job application from the perspective of language as social practice with a focus on practices circumsbribed to the work sphere. This way, the struture of the texts within this system of genres is analyzed using the framework of Systemic-Functional Linguistics (Halliday, 1994; 2004 and Halliday & Hasan, 1989). The texts are analyzed in their organizational patterns and clauses are classified considering the type of processes, according to the System of Transitivity. Besides, the communicative purposes as welll as the characterization of the participants in the activities system are identified. Contrary to initial expectations, the interview was pointed out in the results as the most relevant genre in evaluating the applicants. Overall, the results offer an understanding of the interaction as characterized by specific aims in a particular professional sphere and can be valid for language educators, mainly those who work with Portuguese as mother tongue for instrumental purposes with a focus on professional genres.